2000
DOI: 10.1016/s0022-5347(05)67106-6
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependent Apoptosis and Loss of Rhabdosphincter Cells

Abstract: The dramatic decrease in the number of striated muscle cells in the rhabdosphincter of the elderly due to apoptosis represents the morphological basis for the high incidence of stress incontinence in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 22 publications
5
58
2
1
Order By: Relevance
“…We demonstrated that apoptotic DNA fragmentation increased progressively with age in the human gracilis muscle. These results are in accordance with those presented in the study by Strasser et al (37), who found an increased incidence of apoptosis using a TUNEL assay in human rhabdosphincter skeletal muscle with age. In addition, we have previously reported the age-dependent induction of AIF and a significant increase in DNA fragmentation in the human semitendinosus skeletal muscle (33).…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that apoptotic DNA fragmentation increased progressively with age in the human gracilis muscle. These results are in accordance with those presented in the study by Strasser et al (37), who found an increased incidence of apoptosis using a TUNEL assay in human rhabdosphincter skeletal muscle with age. In addition, we have previously reported the age-dependent induction of AIF and a significant increase in DNA fragmentation in the human semitendinosus skeletal muscle (33).…”
Section: Discussionsupporting
confidence: 93%
“…The urethral sphincter muscle, which is the major muscle responsible for the urinary continent system, is composed of a thin inner layer of smooth muscle and a thick outer layer of striated muscle [24]. Apoptosis of the external rhabdosphincter cells is suggested as one of the major underlying causes of stress urinary incontinence [25]. Thus, although a large part of the low urinary tract symptoms, which are reduction in bladder capacity, uninhibited contractions, and diminished urethral pressure, are related to the aging-bladder itself [26], aging-related reduction of muscle changes can also affect the low urinary tract symptoms [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of the external rhabdosphincter cells is suggested as one of the major underlying causes of stress urinary incontinence [25]. Thus, although a large part of the low urinary tract symptoms, which are reduction in bladder capacity, uninhibited contractions, and diminished urethral pressure, are related to the aging-bladder itself [26], aging-related reduction of muscle changes can also affect the low urinary tract symptoms [24,25]. Because proving the effect of exercise on the pelvic floor muscles or urethral rhabdosphincter muscle in animal models remains difficult, we analyzed the effect of an exercise regimen such as treadmill exercise on the gastrocnemius muscle which is most representative muscle in exercise related research in an old-age rat model to determine the effect of exercise on sarcopenia and the antiaging effect of pelvic floor muscle training.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle atrophy and the loss of myofibers are associated with sarcopenia: a reduction of muscle mass and strength occurring during normal aging in rodents and humans (8,39). The rare reports on the incidence of apoptosis in muscles during normal aging did correlate sarcopenia and the loss of muscle cells with elevated DNA fragmentation in rats and humans (40,41). In this study, the course of apoptosis has been linked to the physiological age of the f ly by taking advantage of variations in longevity resulting from the genetic background.…”
Section: Discussionmentioning
confidence: 99%